MIGRANT LABOUR UPSKILLING – ISSUES AND CHALLENGES FOR SKILL DEVELOPMENT INITIATIVES: - Dr. Rajini, Dr.M.M.Bagali, Vidya S.Patil (Chelonian Research Foundation, 2024)
Today the world is moving towards skill and technology. All sectors are increasingly embracing skilled manpower. Employment protection and opportunity for better earnings are all possible with skilling. Labour productivity can also be achieved with skilling. It is critical from both the socio-economic and demographic points of view. It is an important tool for reducing poverty, enhancing competitiveness and employability and to promote the self-entrepreneurship among youths. However, majority of the workers are employed in the unorganized sector. Working in this unorganized sector provides not much scope for improvement. Migrants constitute a large segment working in the unorganized sector. It is also a well-known fact that because of their inherent drawbacks they are forced to work in the unorganized sector and are exploited. The system of finding work through agents and other means has its own misgivings. They are continuously getting exploited due to the intermediaries in the labour market. The migrant workers face lot of challenges in getting good education, skill training and employment. It is here that the government should step in, if at all they want to make use of the so-called demographic dividend. The government has no doubt taken a great step in this direction by setting up a ministry for skilling and training. Crores of money has been spent on training and placements but the vast majority are still unaware of this herculean effort. The major issue with unskilled migrants is that they are unable to work in the organised sector, which necessitates upskilling. India is not only poised for growth but is growing at a magical pace. When the world is reeling under financial crises, our country is the sun among stars. It is the human resources that has led us to this growth. While skilling and upskilling have all proved its relevance, the government has shown its commitment by enhancing the allocation to skill development initiatives in the present budget. The migrants have expressed their willingness to get trained if some of the bottlenecks are removed. They have stated that the most significant constraints they face are a lack of time after working hours and the possibility of losing daily wages. They are in favour of on-the-job training. However, the unorganized sector does not encourage such training facilities. The government has to bring about a big change in the reach aspect. Also, all these initiatives should be aggressively promoted in the rural areas. Key Words: Migration, Skill development, Government Initiatives.